2007
DOI: 10.1002/mc.20406
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of DNA damage‐induced p53 expression by arsenic: A possible mechanism for arsenic co‐carcinogenesis

Abstract: Inhibition of DNA repair processes has been suggested as one predominant mechanism in arsenic co-genotoxicity. However, the underlying mode of action responsible for DNA repair inhibition by arsenic remains elusive. To further elucidate the mechanism of repair inhibition by arsenic, we examined the effect of trivalent inorganic and methylated arsenic metabolites on the repair of benzo(a)pyrene diol epoxide (BPDE)-DNA adducts in normal human primary fibroblasts and their effect on repair-related protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 53 publications
5
54
1
Order By: Relevance
“…These data demonstrate that in human skin fibroblasts arsenite and MMA(III) more interacts with XPC expression, resulting in decreased XPC protein level and diminished assembly of the NER. The observed stronger impact on XPC by MMA(III) may explain the more potent NER inhibition by MMA(III) as compared to arsenite Shen et al, 2008). Finally, these data provide further evidence that in the case of DNA repair inhibition the biomethylation of arsenic increases inorganic arsenic induced genotoxicity and probably contributes to its carcinogenicity.…”
Section: Arsenicmentioning
confidence: 67%
See 1 more Smart Citation
“…These data demonstrate that in human skin fibroblasts arsenite and MMA(III) more interacts with XPC expression, resulting in decreased XPC protein level and diminished assembly of the NER. The observed stronger impact on XPC by MMA(III) may explain the more potent NER inhibition by MMA(III) as compared to arsenite Shen et al, 2008). Finally, these data provide further evidence that in the case of DNA repair inhibition the biomethylation of arsenic increases inorganic arsenic induced genotoxicity and probably contributes to its carcinogenicity.…”
Section: Arsenicmentioning
confidence: 67%
“…Since bulky lesion formation is the possible responsible for their carcinogenicity, genetic integrity depends largely on NER efficiency. Many studies have shown that inorganic arsenic inhibits repair of bulky DNA adducts induced by UV-irradiation Danaee et al, 2004) or benzo [a]pyrene in cultured cells and laboratory animals Shen et al, 2008); additionally arsenite has been shown to downregulate expression of some NER genes in cultured human cells (Hamadeh et al, 2005). In humans, arsenic exposure via drinking water was correlated with a dose relationship dependent to decreased expression of some NER genes and reduced repair of lesions in lymphocytes (Andrew et al, 2006).…”
Section: Arsenicmentioning
confidence: 99%
“…Furthermore, arsenic reduced unscheduled DNA synthesis (UDS) and the excision of CPDs irradiation. The reported studies of NER inhibition by arsenic [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] are summarized in Supporting Information Table S1.…”
Section: Inhibition Of Ner By Arsenicmentioning
confidence: 99%
“…These results differ from those reported by Simoes et al (35) in which no significant difference in p53 expression was found in p53-WT HCT 116 cells after a 24-h exposure to AA (100 μM). Many studies have showed that TP53 is involved in the nucleotide excision repair pathway and that loss of TP53 will enhance DNA damage (48)(49)(50). Shen et al (50) showed that arsenic can cause genotoxicity by inhibiting the p53-medicated nucleotide excision repair.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Many studies have showed that TP53 is involved in the nucleotide excision repair pathway and that loss of TP53 will enhance DNA damage (48)(49)(50). Shen et al (50) showed that arsenic can cause genotoxicity by inhibiting the p53-medicated nucleotide excision repair. Tsai et al (49) showed that arecoline, which is a major alkaloid of areca nut, can repress p53-activated DNA repair and induce DNA damage in human epithelial cells.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%